Pengaruh Pemberian Dosis Pupuk Kasgot (Bekas Maggot) dan NPK Terhadap Pertumbuhan dan Hasil Tiga Varietas Jagung Manis (Zea mays Saccharata Sturt. L) - Liliek Mulyaningsih (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to determine the effect of dosing kasgon and NPK fertilizers on the growth and yield of three varieties of sweet corn (Zea mays Saccharata Sturt. L). This research will be carried out in January 2024 in Dempel village, Geneng District, Ngawi Regency. The study used the RAKL (Complete Group Random Design) method which was arranged in separate plots (Split Plot) with 2 kinds of treatment factors. The results showed: (1) The dose of organic fertilizer K3 (475 grams / polybag) has a real effect on the height and number of leaves so as to increase the yield of sweet corn plant production. (2) V2 variety (super sweet variety) gives the best growth while V3 variety (sweet boy variety) gives the best production yield. (3) The interaction of V2K1 treatment (super sweet variety and organic fertilizer kasgot 275 grams / polybag) provides the best growth in plant height with an average of 224,667 cm. The interaction of V2K3 (super sweet variety and organic fertilizer kasgot 475 grams / polybag) provides the best growth in the number of leaves with an average of 19,667cm.